Flow based network mediation and QOS measurement / Mohd Saufy Rohmad - Rohmad, Mohd Saufy (2010)
Flow based network monitoring is the new telecommunications network monitorin g technique that is used nowadays. With this techniqu e, each TCPfIP flow between sender and receiver will be captured using capturing tool and will be analyzed using specific applications. There are a few issues arised among researchers in the area of flow based network monitoring. This includes the reliability of using flow based traffic repository system. Another issue that arise is the separation between the typical network s monitoring with Quality of service (QoS) monitoring. This research intends to design a simple prototype of flow-based network monitoring for mediation and QoS monitoring. This research also aims to do a detailed inspection of every step of flow based network monitoring . This involves step-by-step experiments from packet capture to flow central collector. The experiments produced the best architecture of flow based system, as well as exposing the advantages and disadvantages of each different option. We are developing the network test bed to test and prove the hypotheses. We also used real traffic capture from a live network as the source of our solution. Both of these techniques (test bed and real traffic capture) were used to produce optimum experiment results. We also used generated traffic from a traffic generato r D-ITG to be used into our system. The experiments were done in order to get a variety of results. This research made severa l new discoveries in the network mediation system and usage of flow based network for QoS measurement.